RNA-seq studies using wheat PHYTOCHROME B and PHYTOCHROME C mutants reveal shared and specific functions in the regulation of flowering and shade-avoidance pathways. Issue 1 (December 2016) - Pearce, Stephen; Kippes, Nestor; Chen, Andrew; Debernardi, Juan; Dubcovsky, Jorge
Abstract Background In cereal crops such as wheat, an optimal timing of developmental transitions is required to maximize grain yield. Many of these developmental changes are precisely regulated by changes in the duration, intensity or quality of light. Phytochromes are dimeric photoreceptors that absorb light maximally in the red and far-red wavelengths and induce large-scale transcriptional changes in response to variation in light quality. In wheat, PHYC is required for early flowering under long days. However, it is currently unknown whether this function requires the presence ofPHYB . In this study, we characterized the role ofPHYB in wheat development and used RNA-seq to analyze and compare the transcriptomes ofphyB -null andphyC- null TILLING mutants. Results Under long-day photoperiods, phyB- null plants exhibit a severe delay in flowering comparable to the delay observed inphyC -null plants. These results demonstrate that both genes are required for the induction of wheat flowering under long days. Using replicated RNA-seq studies we identified 82 genes that are significantly up or down regulated in both thephyB- null andphyC- null mutant relative to their respective wild-type controls. Among these genes are several well-characterized positive regulators of flowering, includingPPD1, FT1 andVRN1 . Eight-fold more genes were differentially regulated only in thephyB -null mutant (2202) than only in thephyC- null mutant (261). ThePHYB- regulated genes were enriched in components of the auxin, gibberellin and brassinosteroid biosynthesis and signaling pathways, and in transcription factors with putative roles in regulating vegetative development and shade-avoidance responses. Several genes involved in abiotic stress tolerance pathways were also found to be regulated byPHYB . Conclusions PHYB andPHYC are both required for the photoperiodic induction of wheat flowering, whereasPHYB alone regulates a large number of genes involved in hormone biosynthesis and signaling, shade-avoidance response, and abiotic stress tolerance. Our analysis provides a comprehensive overview of the PHYB- and PHYC-mediated transcriptional changes during light signaling, and an initial step towards the dissection of this regulatory gene network in wheat. This further dissection will be required to explore the individual phytochrome-mediated developmental responses and to evaluate their potential to improve wheat adaptation to changing environments.